"Failure to adjust": Boston's bid for the 2024 Olympics and the difficulties of learning Olympic wisdom. (November 2019) - Kassens-Noor, Eva
Local resistance often cancels Olympic bids. Boston's infamous bid failure was one of the first that demonstrated how local resistance can diminish boosters' aspirations. As an insider to the bidding process, I trace the adjustment strategies of Boston's bidding committee, B2024, to bid opposition over the course of Boston's 2024 Olympic bid (2014–2015). I analyze the institutional learning that occurred and find B2024 learned through Olympic networks that won Olympic bids. These Olympic networks failed to learn amidst changing local circumstances and applied old solutions to new problems. While facing four crises, B2024 staff learned the complexities of Olympic bidding in a high-pressure learning environment that did not allow for trial and error. Against anti-Olympic movements, B2024 responded with fire-extinguishing techniques rather than plotting an organized strategy. While bidding, city governments must learn from failed bids to attain Olympic wisdom, which requires mastery of Olympic, counter-Olympic, and local knowledge. Using B2024's learning process, I draw lessons for policy on learning and organizing complex projects with tight timelines and high uncertainty.